Better renal replacement therapy to improve sexual function in female patients with end-stage renal disease: A cross-sectional study - Tjahjodjati Tjahjodjati; Steven Steven (Current Urology, 2024)
Abstract. Background. Sexual dysfunction is commonly observed in patients with end-stage renal disease (ESRD). Sexual dysfunction in correlation with ESRD is associated with physiological and psychological problems resulting in low sexual desire, arousal, difficulties in achieving orgasm, and pain during intercourse. Studies on female sexual dysfunction (FSD) in correlation with renal replacement therapy are limited, and previous studies reporting contradictive results have indicated that the best modality for providing better outcomes (especially on FSD) remains unclear. Thus, this study aimed to compare the sexual function between female patients with ESRD who were on continuous ambulatory peritoneal dialysis (CAPD) and those on hemodialysis (HD). Materials and methods. This study enrolled female patients who were randomly selected from the urology and renal division of the Internal Medicine Outpatient Clinic of our hospital from January 2020 to August 2021 and divided into the following groups: predialysis, HD, CAPD, and control groups. The participants were asked to fill out the Female Sexual Function Index (FSFI) questionnaires, and their data were recorded and analyzed using GraphPad Prism 9.0.0. Results. Of the 280 patients, 200 female patients were included in this study. The rate of FSD (cutoff: 26.55) was 42% in the control group, 72% in the predialysis group, 62% in the CAPD group, and 66% the in HD group. The control group had a higher mean score in all parameters (p < 0.05). The total FSFI mean score indicated no significant difference (p > 0.05) between the patients on HD and those on CAPD; the mean of each point was almost identical except for satisfaction, which was higher among patients on CAPD (p < 0.05). Significant differences in the components of desire, arousal, orgasm, and satisfaction were observed between the groups. Conclusions. Patients on CAPD had better FSFI scores than the female patients with ESRD who were on HD, and the scores of both groups of patients were better than those of the predialysis group.